2019
DOI: 10.3390/molecules24030605
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant, α-Amylase and α-Glucosidase Inhibitory Activities and Potential Constituents of Canarium tramdenum Bark

Abstract: The fruits of Canarium tramdenum are commonly used as foods and cooking ingredients in Vietnam, Laos, and the southeast region of China, whilst the leaves are traditionally used for treating diarrhea and rheumatism. This study was conducted to investigate the potential use of this plant bark as antioxidants, and α-amylase and α-glucosidase inhibitors. Five different extracts of C. tramdenum bark (TDB) consisting of the extract (TDBS) and factional extracts hexane (TDBH), ethyl acetate (TDBE), butanol (TDBB), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 90 publications
(69 citation statements)
references
References 46 publications
3
59
0
1
Order By: Relevance
“…The antioxidant capacities of MA, MB, and the mixture of MA and MB (MAB, 1:1, v/v) were evaluated and compared with tricin by 2,2'-azino-bis radical cation (ABTS•+) decolorization, reducing power, and β-carotene bleaching methods which were described previously by Quan et al [17].…”
Section: Antioxidant Activitiesmentioning
confidence: 99%
“…The antioxidant capacities of MA, MB, and the mixture of MA and MB (MAB, 1:1, v/v) were evaluated and compared with tricin by 2,2'-azino-bis radical cation (ABTS•+) decolorization, reducing power, and β-carotene bleaching methods which were described previously by Quan et al [17].…”
Section: Antioxidant Activitiesmentioning
confidence: 99%
“…In this research, the DPPH and ABTS assays were conducted to evaluate the antioxidant activities of the samples. The antioxidant property is mainly characterized by phenolic contents that can effortlessly naturalize free radicals [11]. We found that K2 had higher antioxidant activity in both grain and straw than the original cultivar.…”
Section: Discussionmentioning
confidence: 79%
“…The phenolic contents were also increased with the antioxidant activities. Quan et al [11] assumed that phenolics might not be the only contributors toward the antioxidant properties.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations